Christianity and Ritual: A Study of Church Members in the Practice Ritual of “Buang Soe” - Pontoh, Ryshel (STT Transformasi Indonesia Manado, 2025)
This paper attempts to describe the culture of the Treman community, specifically the rejection of disasters with the ritual of throwing away soe using a socio-theological perspective. This paper aims to describe the meaning of the Treman community who have embraced Christianity, in relation to the practice of the throwing away soe ritual. This paper uses a qualitative method with a case study design. Interviews are a data collection technique to deeply observe the community's understanding in implementing the throwing away soe ritual. The results obtained in this study are that the ritual is indeed carried out by the community when avoiding various accidents and disasters. It is done by worshiping their god. The interesting thing about the implementation of this ritual lies in the community who already believe in Christ, namely Christianity. Such is the social reality that occurs in the village of Treman so that social and theological analysis can be something new to explore the throwing away soe ritual as a cultural practice of the community. Through deep meaning to this ritual, the Treman community not only maintains tradition, but also opens itself to various other spiritual perspectives